Investigation of Learning Loss in the Students' Skills Competency Domain in Islamic Religious Education Subjects at Muhammadiyah Jogokariyan Elementary School - Pradipa, Rafi; Nurchamidah, Nurchamidah; Safingah, Kuni; Hamsah, Muhammad; Rosyad, Ali Miftakhu (SALIHA: Jurnal Pendidikan Islam, 2025)
This study aims to investigate the problem of learning loss in the realm of student skill competencies, especially in Islamic Religious Education subjects due to online learning during the recent pandemic. This study uses a case study method to explore a case related to learning loss in students at Muhammadiyah Jogokarian Elementary School. Data collection techniques were carried out by means of interviews, observations, and documentation to school residents. The results of this study indicate that student learning loss in the psychomotor aspect (skills) experienced by students at Muhammadiyah Jogokariyan Elementary School are that students are unable to understand learning in practice in Islamic Religious Education subjects in a complete, conceptual, and structured manner. Islamic Religious Education teachers also experience obstacles where Islamic Religious Education teachers are unable to understand optimally because they are limited to video media sent by students online, difficulties experienced by Islamic Religious Education students in practicing Islamic Religious Education materials in the form of ablution readings, prayer readings, memorizing letters.